Morphology and thermoluminescence characteristics of customised Ge-doped optical fibre under Am-Be neutron source as a potential to be used for space radiation detector - Bajuri, F.; Bradley, D. A.; Mustafa, S.; Tamchek, N.; Ahmad Saad, F. F.; Mazlan, N.; Mohd Noor, N. (Elsevier, 2022)
In the low Earth orbit (LEO) neutron particles exist from secondary radiations due to interactions of Galactic Cosmic Ray (GCR) or trapped protons in the Earth's inner radiation belt with the Earth's atmosphere or space object materials or the astronaut themselves. Apart from that, high energy neutrons produced during solar activities may survive in the distance travelled to the Earth. For passive dosimetry in space, the presence of neutrons should be considered. In this work, we focused on the capability of Customised Optical Fibres (CusOF) to detect the neutrons produced by 241AmBe neutron source. Also, the morphology of flat fibres (FF) was analysed using scanning electron microscopy (SEM) and Electron Dispersive X-ray (EDX). From the SEM images, ImageJ software was employed to measure the area of the organic shaped core of the FF accurately. From the EDX results, it was found that the effective atomic number of CusOF were in the range of 13.40–15.25, similar to human skeleton. Irradiation of CusOF to 241AmBe neutron source shows that at a distance of 0 cm and 15 cm from the source, CusOF had high coefficient of determination (R2) value of 0.95–0.99, better than that of TLD-100 and TLD-700, 0.86 and 0.92, respectively, at 0 cm. This shows that the CusOF has high potential to be used for neutron radiation detector.